Potential first trimester metabolomic biomarkers of abnormal birth weight in healthy pregnancies. (15th May 2014) - Ciborowski, Michal; Zbucka‐Kretowska, Monika; Bomba‐Opon, Dorota; Wielgos, Miroslaw; Brawura‐Biskupski‐Samaha, Robert; Pierzynski, Piotr; Szmitkowski, Maciej; Wolczynski, Slawomir; Lipinska, Danuta; Citko, Anna; Bauer, Witold; Gorska, Maria; et al.
ABSTRACT Objective Macrosomia and low birth weight (LBW) can be associated with pregnancy complications and may affect the long‐term health of the child. The aim of this study was to evaluate the metabolomic serum profiles of healthy pregnant women to identify early biomarkers of macrosomia and LBW and to understand mechanisms leading to abnormal fetal growth not related to mother's body mass index or presence of gestational diabetes. Method Serum samples from 770 women were collected between the 12th and 14th gestational week. Delivery samples were divided into three groups according to the infant birth weight as follows: low, <2500 g; normal, 2500–4000 g; and high >4000 g. Samples from women with any complications of pregnancy were excluded. Serum fingerprinting was performed by LC‐QTOF‐MS. Results Lower levels of phospholipids, lysophospholipids, and monoacylglycerols; low vitamin D3 metabolites; and increased bilirubin level were associated with macrosomia. Because most changes involved lipids, as a concept of validation, adipocyte fatty acid‐binding protein (A‐FABP) levels were measured and found correlated with the studied lipids and birth weight. Conclusion Serum fingerprinting in early pregnancy can predict the risk of macrosomia. Serum levels of A‐FABP and several lipids are promising prognostic markers for macrosomia in healthy pregnancies. © 2014 John Wiley & Sons, Ltd.